Pengaruh Pelatihan dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. Wahana Karya Sejahtera Mandiri Kabupaten Mamuju Tengah - Hajjad, Mufidatul Nurul (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
Training was born because of the efforts of the institution by working with members to develop knowledge, skills, and ethics that are relevant to their activities. When companies provide effective training, they help employees learn new knowledge, skills and abilities. The formulation of the problem in this research is to see the extent to which training and organizational culture are able to create reliable performance and employees who have good performance as a result can compete and survive from their competitors. The purpose of this research is to find out the influence of training and organizational culture significantly on the work of members at PT. Wahana Karya Sejahtera Mandiri. The research results found . training has more dominant influence than organizational culture. It is shown that PT. The Wahana Karya Sejahtera Mandiri in Central Mamuju Regency is still low. One of the contributing factors is the lack of consistency in implementing the company's organizational culture every day. The results of this research can be a reference for future improvements, especially for employees and for companies in general.